EigenArchitecture - Hovestadt, Ludger; Bühlmann, Vera (Applied Virtuality Book Series, 2014)
A path out of the technological and economical excesses in contemporary architecture:A book on research and education in architecture and information technology, conceived of as philosophical interplay between two species similar in kind. Neither of them is in the least disciplinal: both affect everything, both are arts of structuring. The one 2500 years old and dignified, the other just 50 years of age and impatient.